SOTAGLIFLOZIN SIGNIFICANTLY REDUCES CARDIOVASCULAR DEATH, MYOCARDIAL INFARCTION, AND STROKE IN THE SCORED TRIAL - Deepak L. Bhatt; Michael Szarek; Bertram Pitt; Ph Gabriel Steg; on behalf of the SCORED Investigators (Elsevier, 2023)
Therapeutic Area: Diabetes Background: SGLT2 inhibitors have had a remarkable effect on heart failure, but variable effects on ischemic endpoints. In the SCORED trial, sotagliflozin, a dual SGLT1 and 2 inhibitor, reduced total cardiovascular (CV) deaths, heart failure hospitalizations, and urgent heart failure visits. Additionally, it reduced both total myocardial infarctions (MI) and strokes. Methods: In SCORED, 10,584 patients with type 2 diabetes and chronic kidney disease were randomized to sotagliflozin or placebo; median follow-up was 16 months. Patients in the prespecified subgroups with and without CV disease at baseline were examined for treatment effects on major adverse cardiovascular events (CV death, MI, and stroke). Results: There were 5144 patients with CV disease and 5440 patients without at baseline. In both the patients with and without CV disease, there were significant reductions in CV death, MI, and stroke (HR 0.79 and 0.74, respectively; Figure). The relative risk reductions were very similar in both subgroups, though the baseline rates were expectedly higher in those with CV disease and the absolute risk reduction was 3 times larger. Reductions in total MI (HR 0.69 and 0.66) and stroke (HR 0.69 and 0.62) were individually evident in both subgroups. Sensitivity analyses with various post hoc definitions of CV disease showed generally consistent results. Conclusion: Sotagliflozin significantly reduced total CV death, MI, and stroke in not only patients with prior CV disease, but also in patients without. This difference from all the other SGLT2 inhibitor trials may be due to the additional SGLT1 inhibition provided by sotagliflozin.